IDENTIFICATION OF ETHNOSCIENCE DADIAH (BUFFALO MILK YOGURT) LAMBAH, SIANOK CANYON, BUKITTINGGI AS TYPICAL CULINARY OF WEST SUMATRA - Rehan ramadhani (SEMESTA: Journal of Science Education and Teaching, 2021)
This study aims to look at the ethnosains in the process of making and utilizing dadiah as a traditional food in West Sumatra. This dadiah is a typical food of West Sumatra that uses the characteristics of bamboo as a medium in fermented buffalo milk. It is the powder on bamboo that helps ferment buffalo milk. The bamboo used for making dadiah is bamboo which is often referred to by the local community as "Pariang". dadiah has many benefits, including very good for young pregnant women to give birth. The protein content in dadiah is higher than the protein found in cow's milk yogurt. dadiah can also be used as a beauty by making a face mask with coffee grounds added. Processing of West Sumatra dadiah is also very minimal because only areas that have a lot of buffalo often produce dadiah. It is hoped that dadiah production can be further increased so that the typical food of West Sumatra can become a competitor in the market and better known in the outside world.